Clinical case series on presentations of krait bite envenomation - Shireen Faruque Yakub; Babita Ghodke; Lakshmi Monika Puvvadu; Apoorva Nirmal; Ravi Patil (MGM Journal of Medical Sciences, 2024)
Neurotoxicity is the most peculiar feature of krait envenomation. A patient presenting to the emergency room with complaints of snakebite followed by acute neuromuscular weakness and progressive respiratory involvement should ring a bell for neurotoxic snakebite. The progression of symptoms, muscle involvement and weakness, respiratory worsening, and recuperating post administration of antivenom and acetylcholinesterase inhibitors can vary widely. Delays in diagnosis and administration of treatment are linked to increased mortality rates. In this report, we present cases of krait envenomation, highlighting differences in their management based on each patient’s presentation. All three cases were confirmed krait bites—in two cases, the bystanders had killed and brought the snake to the emergency room, where it was identified as a krait on arrival. Meanwhile, in the third case—based on symptoms, treatment was initiated, and krait was identified a couple of hours later.